Descriptive and Correlation Analysis of Bank Financial Performance on Market Capitalization: Evidence from National Banks in Indonesia (2020–2024) - Yonfrayogo, Armada; Lisnawahnida, Sona Rostiyanti (Cv. Syntax Corporation Indonesia, 2025)
This study examines the relationship between bank financial performance and market capitalization of Indonesian national banks during 2020–2024. Using a quantitative approach with 75 observations, the research analyzes Return on Equity (ROE), Operating Expenses to Operating Income (BOPO), Non-Performing Loans (NPL), and Capital Adequacy Ratio (CAR) as independent variables, with the natural logarithm of market capitalization (LnMC) as the dependent variable. Descriptive statistics reveal variations across banks, with ROE averaging 11.43%, BOPO 75.05%, CAR 24.71%, and NPL at a relatively low level after log transformation. Correlation results show that ROE has a strong, positive, and significant relationship with market capitalization, while BOPO has a significant negative relationship. In contrast, NPL is negatively associated but insignificant, and CAR shows no significant effect. These findings highlight that profitability and efficiency are the main drivers of market capitalization in Indonesian banks, while credit risk and capitalization levels play less important roles. The study contributes to the literature on banking and finance in emerging markets and provides practical insights for bank managers, regulators, and investors in strengthening performance and market value. These findings reinforce signaling theory and agency theory in the context of banking in emerging markets, confirming that profitability and operational efficiency are the primary signals considered by investors in valuing banks. This study provides new empirical evidence on the limited influence of CAR and NPL on market valuation when these ratios are already above strict regulatory thresholds.